Credit Agreement with Guaranteed Certificate of Ownership of Land Made with A Fake Sale and Purchase Deed - Manfaluthi, Agus; Hariyana, Trinas Dewi; Zein, D’ Adellia Dinnary (UNISKA LAW REVIEW, 2023)
Banks always use a certificate of ownership as collateral that accompanies the credit agreement, especially for mortgage credit agreements. Certificates of ownership that are obtained from the selling and buying process need sale and purchase deeds to make the certificates of ownership. The problem is when a fake sale and purchase deed is used to create a certificate of ownership and the certificate is used as collateral in a credit agreement. So the question is the legal status and implications of credit agreements that use title certificates made with fake sale and purchase deeds. To answer this question, this study uses normative research methods with a legal approach and a case approach. The result of his research is that in making a credit agreement, banks have their own rules and principles that must be followed before agreeing to the credit agreement included in the assessment of collateral. Based on the case related to this matter contained in decision number 65/Pdt. G/2018/PN.Gpr., the panel of judges of the Kediri Regency District Court ruled that credit agreements using title certificates made using fake sale and purchase deeds were valid. The ratio decidendi of the judges is because the bank has carried out procedures according to the law when making credit agreements. and the transfer of title certificates is considered non-existent because there is a legal defect in the transition process, namely by the existence of a fake sale and purchase agreement Deed.